2021
DOI: 10.1039/d1ta01906f
|View full text |Cite
|
Sign up to set email alerts
|

Melt-quenched porous organic cage glasses

Abstract: The melting and glass-forming behaviour of a range of organic cages was investigated, with quenching of melted liquid states providing molecular glasses, one of which exhibited improved gas uptake compared to the starting amorphous cage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…As a material assembled from discrete molecules, one unique feature is the polymorphism of the cage molecules, which could be used for introducing the desired responsiveness of the material when stimulated by solvents, heat, or light. Transforming the crystalline cages into an amorphous state leads to the already booming area in creating cage glasses [138][139][140] or cage-based porous liquids. 141,142 (5) Solve the outstanding issues preventing industrial application.…”
Section: Discussionmentioning
confidence: 99%
“…As a material assembled from discrete molecules, one unique feature is the polymorphism of the cage molecules, which could be used for introducing the desired responsiveness of the material when stimulated by solvents, heat, or light. Transforming the crystalline cages into an amorphous state leads to the already booming area in creating cage glasses [138][139][140] or cage-based porous liquids. 141,142 (5) Solve the outstanding issues preventing industrial application.…”
Section: Discussionmentioning
confidence: 99%
“…While they display low BET surface areas, their CO 2 and methane (CH 4 ) uptakes are similar to ZIF glasses. 39 Other examples of porous organic glassy materials are polymers of intrinsic microporosity (PIMs), rst reported by Budd et al, which are amorphous, nanoporous organic materials with pore sizes in the range of 5.2 to 10.7 Å. [40][41][42] The porosity within PIMs is intrinsic in nature, and results from the inefficient packing of their rigid and contorted macromolecular chains.…”
Section: Methods For Increasing Porosity In Existing Glassesmentioning
confidence: 99%
“…While this study did not yield a type I permanently porous liquid at room temperature, this was the rst reported example of meltable shape-persistent POCs, which recently has led to the liquid phase being exploited in the formation of meltquenched molecular organic cage glasses. 25 In addition, while the formation of a melt-quenched glass with glass transition was not formally noted, it is also worthwhile to mention that one of the alkylated POCs from the initial type I porous liquid study was reported to also have a glassy appearance, namely the n-octyl decorated POC. 21 It was not until 2015 that the rst systems formally identied as porous liquids were reported, where both type I and type II porous liquids, based on hollow silica spheres and POCs respectively, were realised.…”
Section: Key Milestones In the Development Of Porous Liquidsmentioning
confidence: 99%